THE EFFECT OF HUMAN RESOURCE COMPETENCY AND COMPENSATION ON EMPLOYEE PERFORMANCE AT PERUM JASA TIRTA II - Tri Satria Nugroho Putra; Budi Rismayadi; Neni Sumarni (Jurnal Ekonomi, 2022)
The purpose of this research is to obtain empirical evidence and find clarity of phenomena and conclusions about the effect of competence and compensation of human resources on employee performance at Perum Jasa Tirta II. This research was conducted with descriptive quantitative methods and verification. The data analysis technique used is path analysis technique. From the results of research data analysis, the following conclusions are obtained: Competence at Perum Jasa Tirta II is very good, Compensation at Perum Jasa Tirta II. already good, the performance of employees at Perum Jasa Tirta II is very good. There is a strong correlation between competence and compensation, there is a partial effect between competence and compensation on employee performance, and there is a simultaneous effect between competence and compensation on the performance of Perum Jasa Tirta II employees.